The Effect of Pelvic Rocking Exercise with a Birth Ball and SP6 Acupressure on Duration of the First and Second Stage of Labor - Karningsih Karningsih; Dwi Purwanti; Fauziah Yulfitria; Gita Nirmala Sari; Een Nuraenah (Nurse Media Journal of Nursing, 2022)
Background: Long duration of labor increases the pain that a mother experiences. Several non-pharmacological methods, such as pelvic rocking exercises and SP6 acupressure, have been discovered to reduce pain and accelerate labor duration. It needs to be clarified which of the two methods is more effective.Purpose: This study aimed to assess the effectiveness of pelvic rocking exercise with a birth ball and SP6 acupressure in shortening the duration of the active phase in the first and the second stage of labor.Methods: This study used a quasi-experimental design involving 64 mothers in the first stage of normal delivery who were recruited using propensity score matching sampling. The participants were divided into two intervention groups (the pelvic rocking exercise with a birth ball and SP6 acupressure). Each respondent in the two intervention groups was monitored for progress of labor during the active phase in the first stage using a partograph starting from cervical dilatation of 4 cm to 10 cm. The duration of the second stage was assessed by calculating the length of time from cervical dilatation of 10 cm to the delivery of the entire baby. The Mann-Whitney U test was performed to assess the difference between the two interventions in the two stages of labor assessed.Results: There was a difference in the duration of labor in the first stage (p=0.00) and the second stage (p=0.001) between the groups given the pelvic rocking exercise with a birth ball and the SP6 acupressure. The pelvic rocking exercise with a birth ball was found to be more effective in shortening the duration of the active phase in the first stage (Mean rank=19.83) and the second stage of labor (Mean rank=24.56) compared to SP6 acupressure (Mean rank of the first stage=45.17 and Mean rank of the second stage=40.44).Conclusion: The pelvic rocking exercise was found to be more effective compared to SP6 acupressure in shortening the duration of the active phase in the first and the second stage of labor. Pelvic rocking exercise can be implemented to help accelerate labor duration so that mothers can feel more comfortable during the labor.